Simulation of a floating solar farm in waves with a novel sun-tracking system - Wei, Yujia; Ou, Binjian; Wang, Junxian; Yang, Liang; Luo, Zhenhua; Jain, Sagar M.; Hetharia, Wolter R.; Riyadi, Soegeng; Utama, I Ketut Aria Pria; Huang, Luofeng (IOP Publishing, 2023)
The awareness of the energy and climate crisis has accelerated the development of renewable energy sources. Photovoltaic (PV) solar power plants harvest clean solar energy and convert it to electricity, which will be one of the most promising alternatives to the power industry in the context of a low-carbon society. Due to its low power density, the traditional deployment of PV systems on land or inland rivers requires much space. Therefore, industries are increasingly interested in expanding offshore Floating PhotoVoltaics (FPV) to oceans, where FPV has less influence on the marine environment and does not occupy precious space for land resources and human activities. This study performs a hydrodynamics-based structural response analysis for a novel FPV system in OpenFOAM. The wave-proof FPV platform is newly designed for this work, which integrated breakwater technologies to sustain the system's survivability in harsh ocean-wave environments. Firstly, the rational mooring types for FPVs installed close to the island are studied considering seabed effects. Subsequently, extensive parametric studies have been conducted to determine a rational design strategy for the mitigation of wave impact. Several potential effects of the proposed platforms on the hydrodynamics in a coastal sea are evaluated for the first time.
12th International Workshop on Ship and Marine Hydrodynamics (IWSH-2023) 28/08/2023 - 01/09/2023 Aalto University, Espoo, Finland